2016
DOI: 10.1021/acs.joc.6b00558
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Water-Soluble Cyclophane Hexamers Having a Triphenylene Core and Their Enhanced Guest-Binding Behavior

Abstract: A key compound, a precursor of water-soluble cyclophane hexamer, was prepared via Williamson ether synthesis of tetraaza[6.1.6.1]paracyclophane derivatives bearing a bromoacetamide moiety with triphenylene-2,3,6,7,10,11-hexaol as a core. A cationic cyclophane hexamer (1) was obtained by removing the protecting groups from the precursor. Fluorescence titration experiments proved that cationic cyclophane hexamer 1 showed macrocyclic multivalency effects; i.e., 1:1 host/guest binding constants (K) of 1 with anion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Applications have been proposed in electrophotography and organic electronics 2 , organic LEDs 3 , optoelectronics 4 , surface modification 5 , chemical sensing 6 , as optical compensating films for increasing the angle of view of liquid crystal displays 7 , for controlling aggregation of nanoparticles 8 and the templating of inorganic mesostructures 9 . Recently other applications for triphenylene derivatives (not dependent on the self assembly properties) have been suggested, as covalent scaffolds for organised macromolecular structures 10 , molecular receptors 11 and drug delivery systems 12 . All these applications rely on rational modification of the molecular properties via the tailoring of the triphenylene side chains.…”
Section: ! "mentioning
confidence: 99%
“…Applications have been proposed in electrophotography and organic electronics 2 , organic LEDs 3 , optoelectronics 4 , surface modification 5 , chemical sensing 6 , as optical compensating films for increasing the angle of view of liquid crystal displays 7 , for controlling aggregation of nanoparticles 8 and the templating of inorganic mesostructures 9 . Recently other applications for triphenylene derivatives (not dependent on the self assembly properties) have been suggested, as covalent scaffolds for organised macromolecular structures 10 , molecular receptors 11 and drug delivery systems 12 . All these applications rely on rational modification of the molecular properties via the tailoring of the triphenylene side chains.…”
Section: ! "mentioning
confidence: 99%
“…Such disaggregation of the coaggregates was also conducted by other external stimuli such as salts and competitive guests. The design and synthesis of dabsyl-appended cyclophanes described here are applicable to host–drug conjugates because a drug moiety such as doxorubicin , and daunorubicin , may be employed in place of the dabsyl moiety. Such supramolecular coaggregates composed of the host–drug conjugates have potential for use as a drug delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the cyclophane binds selectively to histone proteins, increasing fluorescence intensity significantly. Furthermore, Hayashida and co-workers 52 have reported an anionic water-soluble tetraaza[6.1.6.1]paracyclophane hexamer with a luminescent triphenylene core, which displays multiple binding sites. The authors investigated its association properties towards guests employing fluorescence spectroscopy.…”
Section: Different Types Of Fluorescent Cyclophanesmentioning
confidence: 99%
“…3.1 Anionic cyclophane-based drug carrier. Hayashida and coworkers 52 have investigated (Fig. 37a) the anionic cyclophane hexamer 104 with a triphenylene fluorescent core for encapsulating anticancer drugs.…”
mentioning
confidence: 99%